2005
DOI: 10.1177/0886260505281439
|View full text |Cite
|
Sign up to set email alerts
|

Child Physical Abuse and Self-Perceived Social Isolation Among Adolescents

Abstract: This research examines the connection between physical abuse and social isolation. Using data from the National Youth Survey, a measure of self-perceived social isolation was constructed indicating the extent to which respondents feel detached from their friends and from school. Those who had experienced violence were predicted to be more isolated than those who had not. Results strongly supported the hypothesis, controlling for theoretically relevant variables. Explanation is provided in terms of damage to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
(40 reference statements)
5
40
0
1
Order By: Relevance
“…It may be harder to establish social support networks in environments with high rates of robberies and break-ins, or when one is fearful of others who may perpetrate a crime, which in turn may negatively affect perceived social support and loneliness. Elliott and colleagues’ (2005) study on adolescents, which found that those from riskier neighborhoods were more socially isolated, provides some evidence for this explanation. However, low social support may also predispose individuals to being the target of crime and could be a possible explanation for the association if current social support is consistent with social support at the time of exposure to crime-related trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It may be harder to establish social support networks in environments with high rates of robberies and break-ins, or when one is fearful of others who may perpetrate a crime, which in turn may negatively affect perceived social support and loneliness. Elliott and colleagues’ (2005) study on adolescents, which found that those from riskier neighborhoods were more socially isolated, provides some evidence for this explanation. However, low social support may also predispose individuals to being the target of crime and could be a possible explanation for the association if current social support is consistent with social support at the time of exposure to crime-related trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to overeating, future research should also consider physical inactivity and sedentary behavior as potential responses to abuse. Abused individuals generally show signs of isolation from the community [17,32,33] as a way to protect themselves from potential abusers. However, such behavior may cause a decrease in physical activity and an increase in sedentary behavior [34] which in turn may contribute to the development of overweight.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that abused children have difficulty getting along with other people [19], [20]. The reason for this may stem from a deficit in the ability to recognize the facial expressions of others and infer their beliefs and emotions from these expressions.…”
Section: Introductionmentioning
confidence: 99%